HALAL PRODUCT GUARANTEE IN INDONESIA: REGULATION AND SOCIAL INCLUSION - Muslimin, JM (IAIN Surakarta, 2019)
Halal Product Guarantee Act exists to ensure the protection of halal products consumed by Muslim consumers. Since it contains rules that only lead to protecting certain segments of society (Muslim consumers), this rule has become controversial. It is alleged to be potentially discriminatory. An argumentative and critical study shows that this is not factual. Apart from being legally tested, the social facts show that the regulation can be a means for the process of social inclusion: a process where people can respect each other?s communal rights, within the framework of authentic legal togetherness. The method employed is the analysis of legislation in a sociological perspective (sociological jurisprudence). The results of this study are through a series of juridical and sociological examinations, the Halal Product Guarantee Act can qualify as an integrative factor (social inclusion), in doing so it is expected to be an instrument of protecting people's rights (Muslim consumers' rights to get guaranteed halal products). Keywords: social inclusion, regulation, halal product guarantee, consumer protection.